1997
DOI: 10.1101/gad.11.2.241
|View full text |Cite
|
Sign up to set email alerts
|

An unusual form of transcriptional silencing in yeast ribosomal DNA.

Abstract: Generalized transcriptional repression of large chromosomal regions in Saccharomyces cerevisiae occurs at the silent mating loci and at telomeres and is mediated by the silent information regulator (SIR) genes. We have identified a novel form of transcriptional silencing in S. cerevisiae in the ribosomal DNA (rDNA) tandem array. Tyl retrotransposons marked with a weakened URA3 gene (Tyl-mURAS) efficiently integrated into rDNA. The tnURA3 marker in rDNA was transcriptionally silenced in a SIR2-dependent manner.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
561
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 558 publications
(584 citation statements)
references
References 67 publications
23
561
0
Order By: Relevance
“…Indeed, it had previously been observed that a Pol III reporter gene could be silenced in a SIR-dependent manner (Schnell and Rine, 1986). However, in contrast to early indications (Smith and Boeke, 1997), subsequent more sensitive analysis indicates that SIR2 does not affect rDNA transcription , but may instead affect firing of origins of rDNA replication (Pasero et al, 2002).…”
Section: Esa1p Is a Distinct Rdna Silencing Protein Important For Nucmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, it had previously been observed that a Pol III reporter gene could be silenced in a SIR-dependent manner (Schnell and Rine, 1986). However, in contrast to early indications (Smith and Boeke, 1997), subsequent more sensitive analysis indicates that SIR2 does not affect rDNA transcription , but may instead affect firing of origins of rDNA replication (Pasero et al, 2002).…”
Section: Esa1p Is a Distinct Rdna Silencing Protein Important For Nucmentioning
confidence: 99%
“…Many questions remain about the nature of the regulation of the transcriptional silencing of the remainder of the repeats (reviewed in Grummt and Pikaard, 2003). When it was discovered that Pol II-regulated genes that are engineered into the rDNA array are silenced in an epigenetic manner that is dependent on SIR2 (Bryk et al, 1997;Fritze et al, 1997;Smith and Boeke, 1997), the appealing possibility was raised that Pol I transcription itself might be at least partially regulated through heterochromatin-like SIR-dependent mechanisms. Indeed, it had previously been observed that a Pol III reporter gene could be silenced in a SIR-dependent manner (Schnell and Rine, 1986).…”
Section: Esa1p Is a Distinct Rdna Silencing Protein Important For Nucmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the age-dependent mortality, cell viability at different days of growth was compared by spreading serial dilutions (1 : 10) of the cultures on solid YPD plates followed by incubation at 30 uC for 3 days. Replicative life-span determinations were performed by micromanipulation, as described elsewhere (Smith & Boeke, 1997;Sinclair & Guarente, 1997), using a Singer MSM system 300 micromanipulator. Life-span analyses wer carried out on YPD plates twice independently with 60 cells per strain per experiment.…”
Section: (Adh)mentioning
confidence: 99%